The impact of crisis management on supply chain management to improve the performance continuity in the security sector in Abu Dhabi in the UAE - Abdulla Mohamed, Khalifa Mohamed (2022)
The United Arab Emirates is one of the most attractive countries for tourism and investment, it places additional strains on the country's public security sector in order to maintain the highest levels of safety and security., especially in the capital of the UAE, Abu Dhabi. It is known that effective crisis management contributes significantly to supply chains to ensure the continuity of civil activities in the country. Therefore, this study aims to explore the impact of effective crisis management functions on supply chain management in order to ensure business continuity in the security sector in Abu Dhabi. The study adopted leadership theory and communication theory in situational crises. The proposed conceptual framework explains the relationship between the practices of crisis management, supply chain management, and performance continuity. The research design in this study is scientific the research in this study is scientific, deductive, exploratory, and quantitative. This study employed questionnaires like those employed in the previous studies., which were adopted from previous studies. The population of this study is all employees who work in fields related to national security and their number is estimated to be at least 10,000 civil and military employees the target sample is 366 employees. As for the predictive model of performance continuity, the results show that the sub-model has moderate statistical significance as it can predict 49.8% of the variance in the continuity of performance based on the three predictors and supply chain management. The study showed that supply chain management plays an important mediating role, and the arrangement of the three independent variables is public relations, followed by the crisis management team, and then the crisis management strategy.